PENGARUH INFLUENCER, ULASAN PENGGUNA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN BRAND KAHF DI MEDIA SOSIAL (STUDI KASUS GEN-Z DI KOTA SUMBAWA BESAR) - Fakhri Ramadhan; Tomy Dwi Cahyono (Jurnal Nusa Manajemen, 2026)
This study is motivated by the rapid growth of social media as a medium for digital marketing, particularly for men’s skincare brands such as Kahf, which are widely favored by Generation Z. The objective of this research is to analyze the influence of influencers, user reviews, and product quality on consumer purchasing decisions for the Kahf brand through social media, focusing on Generation Z in Sumbawa Besar. This study employed a quantitative approach with an associative research design, involving 100 respondents selected through purposive sampling. Data were collected using questionnaires and analyzed with multiple linear regression. The findings reveal that all three independent variables—influencers, user reviews, and product quality—have a positive and significant effect on purchasing decisions, both partially and simultaneously. These results highlight that influencer credibility, the authenticity of user reviews, and high product quality are key factors in building consumer trust and driving purchase decisions. In conclusion, leveraging digital marketing strategies through influencer collaboration, effective management of user reviews, and continuous product quality improvement are essential for companies to strengthen competitiveness in the era of social media–based marketing.